1999
DOI: 10.1111/j.1600-0536.1999.tb06203.x
|View full text |Cite
|
Sign up to set email alerts
|

Acetone has anti‐inflammatory effects on experimental contact reactions

Abstract: The effects of a topically applied corticosteroid and its acetone vehicle on experimental allergic, toxic and irritant reactions are presented. The corticosteroid budesonide in acetone or acetone alone was applied to reactions immediately after and at different time intervals within the 1st h after provocation. Classical naked eye observation was performed and the dermal cellular infiltrate was differentiated and counted using a previously well-characterized method. "Treatment", whether with the steroid in ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…However, PK3 microparticles did not display any significant increase in airway inflammation above the saline control, as opposed to PLGA microparticles, which did induce a significant macrophage infiltration starting at day 4 and continuing through day 7 and a transient lymphocyte infiltration at day 4. The extreme biocompatibility of polyketals in the lung may be due to the reported anti-inflammatory activity of its degradation product, acetone [30]. However, further studies would be required to elucidate the mechanism of this PK3 action.…”
Section: Discussionmentioning
confidence: 99%
“…However, PK3 microparticles did not display any significant increase in airway inflammation above the saline control, as opposed to PLGA microparticles, which did induce a significant macrophage infiltration starting at day 4 and continuing through day 7 and a transient lymphocyte infiltration at day 4. The extreme biocompatibility of polyketals in the lung may be due to the reported anti-inflammatory activity of its degradation product, acetone [30]. However, further studies would be required to elucidate the mechanism of this PK3 action.…”
Section: Discussionmentioning
confidence: 99%
“…Akin to acetylacetone the ketone bodies -acetoacetate, h-hydroxibutyrate and acetone -are also CH acidic. Ketone bodies reportedly counteract certain inflammatory processes (Sato et al, 1992;Sjogren et al, 1999). We have studied the effects of ketone bodies on MIF's enzymatic activity.…”
Section: Introductionmentioning
confidence: 99%
“…There is interest in the development of novel anti‐inflammatory agents that could serve as useful therapeutic adjuncts to topical steroids which, though effective and widely used, have a range of unwanted side effects (8). In a recently published study on guinea pig skin, Sjögren et al (9) reported an unexpected finding – that topically applied acetone had anti‐inflammatory effects on experimental contact reactions. The mechanism for this effect is unclear.…”
mentioning
confidence: 99%